Some radio tracer studies of thorium oxidesolution interface - Singh V.N.; Mishra S.P.; Srivastava H.N. (My University, 2025)
Thorium oxide is one of the most important refractory materials used in ceramic industries. In the present work, the surface properties of this oxide have been studied by allowing the adsorption of bromide ions on its surface at various temperatures (5° to 45°C) and pH (3.2 to 11.5) of KBr solutions using Br-82 as tracer. The influence of neutrons and γ-rays irradiations of this oxide by 300 me (Ra-Be) source for 12, 24, 36 and 48 hours on the adsorption of bromide ions has also been studied. The kinetics of adsorption in all the above cases were found to be of first order. It has been observed that the change in temperature, pH and irradiations with neutron and y-rays of the oxide have remarkable effect on the surface behaviour of the adsorbent. The energy of activation of the process has been determined to understand the mechanism of adherence of ions on the surface of thorium oxide. Attempts have also been made to explain the results obtained in the present investigation in the light of some 'adsorptive properties' of thoria in electrolyte solution. © 1981 Taylor & Francis Group, LLC.